Obraz świata po potopie według Rdz 8,22 - Napora, Krzysztof (Verbum Vitae, 2017)
In the face of the majestic conclusion of the flood narrative in Gen 9,1-17, the short text in Gen 8,20-22 seems sometimes to be neglected in biblical literature or considered as only a side issue. In our article, we focus on the promise of God concerning the organization of the cosmos after the flood cataclysm, trying to show the extent and theological depth of the biblical author's vision in Gen 8,22. In his view, God's promise is not limited to a purely temporal re-organization of the cosmos after the cataclysm. Rather, it evokes the principles of the primordial organization of the cosmos established in the original creation act.